Secondary parkinsonism associated with focal brain lesions - Berlot, Rok; Pavlović, Anđela; Kojović, Maja (Frontiers in Neurology, 2024)
Focal imaging abnormalities in patients with parkinsonism suggest secondary etiology and require a distinctive clinical approach to diagnosis and treatment. We review different entities presenting as secondary parkinsonism associated with structural brain lesions, with emphasis on the clinical course and neuroimaging findings. Secondary parkinsonism may be due to vascular causes, hydrocephalus, space-occupying lesions, metabolic causes (including acquired hepatocerebral degeneration, diabetic uremic encephalopathy, basal ganglia calcifications, osmotic demyelination syndrome), hypoxic-ischaemic brain injury, intoxications (including methanol, carbon monoxide, cyanide, carbon disulfide, manganese poisoning and illicit drugs), infections and immune causes. The onset can vary from acute to chronic. Both uni-and bilateral presentations are possible. Rigidity, bradykinesia and gait abnormalities are more common than rest tremor. Coexisting other movement disorders and additional associated neurological signs may point to the underlying diagnosis. Neuroimaging studies are an essential part in the diagnostic work-up of secondary parkinsonism and may point directly to the underlying etiology. We focus primarily on magnetic resonance imaging to illustrate how structural imaging combined with neurological assessment can lead to diagnosis. It is crucial that typical imaging abnormalities are recognized within the relevant clinical context. Many forms of secondary parkinsonism are reversible with elimination of the specific cause, while some may benefit from symptomatic treatment. This heterogeneous group of acquired disorders has also helped shape our knowledge of Parkinson’s disease and basal ganglia pathophysiology, while more recent findings in the field garner support for the network perspective on brain function and neurological disorders.